2014
DOI: 10.2174/1574887108666131213120816
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Fluids in Severe Septic Patients - A Cost-effectiveness Analysis Informed by Recent Clinical Trials

Abstract: Fluid resuscitation with colloids is an established second line therapy for septic patients. Evidence of relative efficacy outcomes is tempered by considerations of the relative costs of the individual fluids. An assessment of recent large clinical trials was performed, resulting in a ranking in the efficacy of these therapies. Probabilities for mortality and the need for renal replacement therapy (RRT) were derived and used to inform a decision analysis model comparing the effect of crystalloid, albumin and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
0
16
1
Order By: Relevance
“…Such considerations gain even more importance when evaluating the potential cost-effectiveness of employing albumincontaining solutions in critically ill patients, and patients with severe sepsis or septic shock, because of their relative high cost. In fact, although as estimate, recent cost-effectiveness analyses have suggested that albumin administration may be the most cost-effective treatment, as compared with other colloids or crystalloids, in septic patients, when considering all the medical costs implied in patient clinical treatment [53].…”
Section: Albumin Administration In Sepsis: the Meta-analysesmentioning
confidence: 99%
“…Such considerations gain even more importance when evaluating the potential cost-effectiveness of employing albumincontaining solutions in critically ill patients, and patients with severe sepsis or septic shock, because of their relative high cost. In fact, although as estimate, recent cost-effectiveness analyses have suggested that albumin administration may be the most cost-effective treatment, as compared with other colloids or crystalloids, in septic patients, when considering all the medical costs implied in patient clinical treatment [53].…”
Section: Albumin Administration In Sepsis: the Meta-analysesmentioning
confidence: 99%
“…Five evaluations examined antibiotic interventions [22][23][24][25][26], two examined fluid therapies [27,28], eight examined EGDT or other (primarily emergency department [ED]-based) resuscitation protocols [35][36][37][38][39][40][41][42]71], three examined procalcitonin algorithms [29][30][31], two examined immunoglobulin therapies [32][33][34], four examined methods of pathogen identification [43][44][45][46], one examined point of care lactate testing [47], and one examined immediate ICU admission [48]. The remaining 20 evaluations examined interventions no longer used in clinical practice-13 examined drotrecogin alfa (activated) (51-64), and seven examined monoclonal antibodies [64][65][66][67][68][69][70].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The reporting quality varied widely, with scores ranging from 13% (3/23) [65] to 95% (21/22) [42,50]. Twelve (26%) of the studies were found to be of excellent [22][23][24][25][26] Fluid therapies 2 (4%) [27,28] Procalcitonin algorithms 3 (7%) [29][30][31] Immmunoglobulin therapies 2 (4%) [32][33][34] EGDT or other sepsis protocol 8 (17%) [35][36][37][38][39][40][41][42][43] Pathogen identification 4 (9%) [44][45][46][47] Other 2 (4%) [48,49] Interventions no longer in clinical practice reporting quality, 18 (39%) of very good quality, 11 (24%) of good quality, and 5 (11%) of poor quality. The quality of evaluations published in the past 15 years was higher (average 75%) than evaluations published prior to 2005 (average 58%), with the quality of evaluations varying by intervention-88% of EGDT and resuscitation protocol evaluations were of very good or excellent quality compared to 60% of evaluations of antibiotic therapies and 25% of evaluations of pathogen identification (Additional file 4).…”
Section: Reporting Qualitymentioning
confidence: 99%
“…A subgroup analysis of a major intensive care fluid therapy trial has indicated a survival benefit for septic patients given albumin . This has contributed to another trial for albumin in sepsis . In contrast, a report from the UK showed randomized trials of human albumin for adults with sepsis does not support a recommendation for use .…”
Section: Therapeutic Strategiesmentioning
confidence: 99%